The Effect of Spirulina Platensis Extract (Arthrospira platensis) on Enhancing Hemoglobin Levels in Pregnant Women - Ratte Putri Anggraeni; Finta Isti Kundarti; Ira Titisari (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
The prevalence of anemia is still relatively high in the world. The impacts of this case are abortion, premature birth, premature rupture of membranes, histitis, postpartum hemorrhage, low birth weight (LBW), risk of congenital defects, infection in babies, and even death. The objective of this research was to assess how the use of spirulina platensis extract influences the elevation of hemoglobin levels in expectant mothers. In this case, the method used is Quasi-Experiment through a pretest and posttest control group design with a sample of 60 participants, consisting of 30 participants and a control group of 30 participants. Furthermore, the group subjected to the intervention was provided with a remedy, which involved administering Spirulina platensis extract in the form of one 300 mg capsule once a day for 30 days and standard care, while the control group received standard care only. In addition, the sampling technique used is simple side random. The results of the Paired Sample T-test analysis in the intervention group during the pretest obtained a mean hemoglobin level of 9.63 with a standard deviation of 0.490, while during the post-test, obtained mean score of 10.93 with a standard deviation of 0.907 with a p-value of 0.000. Meanwhile, the analysis of the control group during the pretest obtained mean hemoglobin levels of 9.60 with a standard deviation of 0.498, while during the posttest, the mean score obtained was 9.70 with a standard deviation of 0.535 and p-value of 0.083. The difference between the mean hemoglobin levels during the posttest in the experimental and control groups showed m equal 10.93; SD equal 0.907 vs. m equal 9.70; SD equal 0.535, with a p-value of 0.000. Therefore, it is summed up that there was an increase in hemoglobin levels in pregnant women after the administration of Spirulina platensis extract. As input for the health workers, especially midwives, it is suggested to offer alternative therapeutic approaches for pregnant women suffering from anemia by applying Spirulina platensis.